Evaluation of the Implementation of Early Children Education Programs in the Rose Playing Group, FKIP Unpatti - Rosmaryn Tutupary; Emma Rumahlewang (International Journal of Education, Information Technology, and Others, 2020)
The objectives of this study are 1) To describe the effectiveness of the implementation of the Early Childhood Education program in the Mawar Play Group FKIP Unpatti in terms of context, input, process, and product variables. 2) To reveal the obstacles or obstacles in the implementation of the PAUD program at KB Mawar FKIP Unpatti and alternative solutions. This research was conducted at KB Mawar in 2019, using two research approaches, namely quantitative and qualitative. From this research found. 1) The results of the evaluation of the PAUD program at KB Mawar using the CIPP model program evaluation are very effective. 2) The obstacles faced in implementing the PAUD program at KB Mawar are the low level ofknowledge stakeholder about the program mission, the existence of facilities and infrastructure, the program management process, the cooperation and participation process, and academic achievement. Efforts that can be made to overcome these obstacles are by extracting community support, improving people's perspective, socializing programs, arranging equipment, materials and study rooms, planning budgets, procuring tools, materials and learning spaces in stages